Photonic sensor based quaternary metal oxide semiconductor by controlling of solar photon intensity - Yildiz, K.; Yeriskin, S. Altindal; Khalkhali, A.; Dere, A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2025)
The photonic sensor comprising of p-type silicon and quaternary ZnCdNiTiO2 metal oxide with ratio of (4;2;2;2) were produced and then electric and optoelectronic characteristics of them were investigated to use current-voltage (IV) characteristics both in the dark/sun photon intensities in broad range of illumination (20-140 mW/ cm2) and voltage range of +/- 5 V. The main physical parameters of the sample have been extracted utilizing various calculation techniques such as thermoionic emission (TE) theory, Cheungs' method and Norde's method which correspond different forward bias voltages. Some differences observed among the electronic parameters can be attributed to the measurement technique, in other words to the voltage dependence. While the Phi Bo decreases linearly with illumination, n exhibits increasing trend. The concentration distribution of the interface traps (Nss) was calculated by using forward-bias (IF-VF) characteristics by considered voltage dependent of n(V) and potential barrier (Phi B(V)) in the dark/illumination conditions. The photonic properties dependence of the fabricated photosensor was explored through the photocurrent (Iph), photosensitivity (S), photo-responsivity (R), and photo detectivity (D*) and these parameters were also found to be voltage dependent. The observed results revealed that a photonic sensor comprising of Al-(ZnCdNi:TiO2)-pSi SD exhibits satisfying rectification and photo-reaction behaviors in a wide sun photon intensity and voltage ranges and hence can be successfully used as a photonic sensor and preferred in the other photonic applications instead of conventional SDs.
Keywords: Quaternary functional semiconductor devices; Photonic sensor; Energy and illumination dependent profile of; interface traps; Conduction mechanisms (CMs)